Pharmacological actions and applications of safflower flavonoids - Ren, Fajian; Tan, Zhen; Hu, Sheng; Rao, Chaolong; Xiang, Qiwen; Wen, Jiayu; Chen, Yan; Peng, Cheng (Frontiers in Nutrition, 2025)
Safflower (Carthamus tinctorius L.), also known as Honghua, blueflower, or prickly safflower, is a medicinal herb effective in promoting blood circulation, dredging meridians, eliminating blood stasis, and relieving pain. Safflower contains complex chemical components, including flavonoids, alkaloids, organic acids, pigments, etc. Among them, flavonoids such as chalcone compounds, quercetin, rutin, and kaempferol serve as the material basis for the pharmacological effects of safflower. Flavonoids in safflower exhibit diverse biological activities, including cardiovascular and cerebrovascular protection, antioxidant, neuroprotective, antitumor, anti-inflammatory, and immunomodulatory effects. Additionally, they show great potential in gynecological diseases, food production, and other fields. With extensive research by scholars on the active mechanisms and targets of safflower flavonoids, their application prospects in the medical field have been found to be extremely broad. This review used keywords such as “Carthamus tinctorius L.,” “safflower,” “flavonoids,” “therapeutic effect,” “mechanism,” “application,” etc., to search relevant studies up to January 2025 in multiple internationally recognized databases (including PubMed, Web of Science, CNKI, Wan fang, Sci Finder, Elsevier, cnipa), finally including 143 high-quality studies. Representative images were drawn using BioRender and ChemDraw software to focus on presenting the action mechanisms and targets of safflower flavonoids. This article systematically reviews the pharmacological effects of safflower flavonoids and their applications in various fields in recent years, aiming to provide theoretical guidance and scientific basis for the comprehensive utilization of safflower resources and further research.